Flower development, pollen viability and pollen storage test of Aeschynanthus radicans - Frisca Damayanti; R Vitri Garvita; Hary Wawangningrum; Sri Rahayu (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Damayanti F, Garvita RV, Wawangningrum H, Rahayu S. 2021. Flower development, pollen viability and pollen storage test of Aeschynanthus radicans. Biodiversitas 22: 1940-1945. Aeschynanthus radicans Jack. commonly-known as lipstick flowers, is an epiphytic plant in Gesneriaceae family. It has an attractive morphology and is easy to grow. Therefore A. radicans is used as mother species for hybridization by plant breeders. The flowers of A. radicans are dichogamous and strongly protandrous. The pollen matures before the stigma becomes receptive and bends away and down when the stigma becomes receptive. As a thought-after material for hybridization, little is known about the flower development, pollen viability, and storability. The purpose of this study was to observe the development phase of A.radicans flowers, determine the viability of pollen during flower development, and investigate the pollen storability at -20?C. Flower development was observed in phases from small buds to anthesis. Pollen viability was tested in 10%, 15%, and 20% sucrose solution for 4 hours. Pollen storage was tested at -20?C for 77 days and tested for viability every three weeks. The best sucrose concentration for the germination of fresh pollen was 20%. The highest pollen viability was at H0 was 58±3% and gradually decreased with flowerage. The lowest viability was 18±14% at flower stage H5, coinciding with the first day of stigma receptive. Pollen storage at -20?C decreased pollen viability to 30,2±2% after 42 days and to 13,54% after 77 days.